PEMBUATAN BERKAKAS (BUNGA DARI KANTONG PLASTIK BEKAS) UNTUK MENINGKATKAN KREATIVITAS KERAJINAN PADA KADER PKK DESA KEDATON KECAMATAN KAPAS BOJONEGORO - Rika Pristian Fitri Astuti; Meiga Ratih Tirtanawati; Siti Ermawati; Taufiq Hidayat; Neneng Rika (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
Plastic is one of the many factors contributing to ecosystem destruction. Unfortunately, in today's era environmental awareness is still very low, and people tend to be indifferent to plastic waste around them. For that, we need a hotfix to fix the problem. New plastic bags can start to decompose for at least 20 years in the soil. If a plastic bag is in water, it will be even more difficult to decompose. (As’ari dkk, 2022). The purpose of this PKM is to increase the creativity of handicrafts in PKK cadres by utilizing used plastic bags waste to make various types of beautiful flowers that have economic and selling value. The method used is lecturing, socializing, and demonstrating. This PKM activity was held on Thursday, May 12, 2022 in Kedaton village. The result of this PKM activity is that PKK women can make handicraft products in the form of beautiful flowers from used plastic bag waste that has economic and selling value. The use of used goods can slightly reduce plastic waste in the community. By processing plastic waste, it can increase creativity and income for mothers because it can create business opportunities. There are also other benefits of processing plastic waste, it can beautify the room, no need to buy flowers, no need to spend a lot of money. The creativity of using used plastic bags in various crafts is a good solution for turning used plastic bags into useful items again. The knowledge and skills gained from this PKM activity are expected to be a provision for entrepreneurship participants through products with plastic-based materials in the field of creative crafts which can be sold and can improve the community's economy. Keywords: plastic bag, creativity, craft